DEVELOPING ENGLISH MODULE FOR THE SEVENTH GRADE STUDENTS OF WALIMANIS INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL - Nurul Khairunnisa; Abd Haris Sunubi; Magdahalena Tjalla (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The objectives of this research are to design of the English module for seventh grade at Walimanis integrated Islamic junior high school and to know the students’ responses to the English module for seventh grade at Walimanis integrated Islamic junior high school. This module is designed to help the students in understanding the existing material individually. This study is being conducted using a research and development (R&D) approach. The participants were junior high school students from Walimanis who were in seventh grade. In an effort to accomplish the goals, the ADDIE model was utilized. The data was collected through questionnaires. It aimed to know the expert's judgment about the module and to know the students' responses.The design of this module is made up of the front cover, back cover, introductory word, content list, basic competence, summary, tasks, exercise, and library list. Based on the result of students’ responses the mean score is 3.65, the acceptability 91%. It is in “high” categories. The result of English teacher’ responses is in “high” categories as well, the acceptability rate in the range of score with 3,50 < X ≤ 3.74 with percentage of 84%-92% have good categories. Thus, it can be concluded that the end result of the development of this module is worthy of being used as a module.